2006
DOI: 10.1002/pmic.200500489
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interacting partners of the neuronal calcium‐binding proteins L‐CaBP1, hippocalcin, NCS‐1 and neurocalcin δ

Abstract: Intracellular Ca2+ signals are transduced by the binding of Ca2+ to sensor proteins, which subsequently modify the activity of their target proteins. Identification of these target proteins is, therefore, important for an understanding of cellular signalling processes. We have investigated the binding partners of four EF-hand Ca2+-binding proteins. Three proteins of the neuronal calcium sensor (NCS) family, hippocalcin, NCS-1 and neurocalcin delta were prepared as N-terminally tagged GST fusion proteins, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
2
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 57 publications
1
61
2
2
Order By: Relevance
“…A study by Couvelard et al found NCALD gene expression to be one of many genes that can distinguish between metastatic and non-metastatic pancreatic endocrine tumor tissue [23]. However, another gene belonging to the same gene family, the neuronal Ca 2+ sensor protein family (NCS), termed VILIP1 [24], has been more extensively studied in cancer, and shown to act as a tumor suppressor gene by inhibiting cell proliferation, adhesion, and invasiveness [25,26]. The VILIP-1 protein and mRNA was down-regulated in a study on non-small cell lung carcinoma [25], and high gene expression was reported to be associated with a high rate of lymph node metastasis and poor prognosis in colorectal cancer patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Couvelard et al found NCALD gene expression to be one of many genes that can distinguish between metastatic and non-metastatic pancreatic endocrine tumor tissue [23]. However, another gene belonging to the same gene family, the neuronal Ca 2+ sensor protein family (NCS), termed VILIP1 [24], has been more extensively studied in cancer, and shown to act as a tumor suppressor gene by inhibiting cell proliferation, adhesion, and invasiveness [25,26]. The VILIP-1 protein and mRNA was down-regulated in a study on non-small cell lung carcinoma [25], and high gene expression was reported to be associated with a high rate of lymph node metastasis and poor prognosis in colorectal cancer patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Other NCS-1 target proteins (Fig. 3) appear to be specific for NCS-1 (Haynes et al 2006). Various studies have implicated NCS-1 in the regulation of VGCCs (Weiss et al 2000;Tsujimoto et al 2002;Dason et al 2009) but there is as yet no evidence for a direct interaction.…”
Section: Calcium Sensor Proteins In Neuronal Functionmentioning
confidence: 99%
“…Many different binding partners have been identified for NCS-1 (Haynes et al 2006;Haynes et al 2007) (Fig. 3) and in some cases these interactions overlap with those of calmodulin (Schaad et al 1996).…”
Section: Calcium Sensor Proteins In Neuronal Functionmentioning
confidence: 99%
“…43,44 NCS-1 exhibits enriched expression in mammalian brain tissue, 45 and many of the aforementioned functions are related to neuronal activity. NCS-1 interacts with a number of targets in common with CaM, 24 and a previous functional study identified links between NCS-1 and CDF of P/Q-type channel activity in rat primary neurons. 20 Other studies have additionally indicated a cellular connection between NCS-1 and P/Q-type channel activity in bovine adrenal chromaffin cells 21,22 and Drosophila .…”
Section: Discussionmentioning
confidence: 82%